2022
DOI: 10.3389/fnsys.2022.941534
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and consciousness in humans and animals – neural and behavioral correlates in an evolutionary perspective

Abstract: Awareness or consciousness in the context of stimulus perception can directly be assessed in well controlled test situations with humans via the persons’ reports about their subjective experiences with the stimuli. Since we have no direct access to subjective experiences in animals, their possible awareness or consciousness in stimulus perception tasks has often been inferred from behavior and cognitive abilities previously observed in aware and conscious humans. Here, we analyze published human data primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 186 publications
0
6
0
1
Order By: Relevance
“…The NDE definition by Charland-Verville et al (2020) and the consideration that some situations of NDEs may refer to disconnected consciousness as, for example, observed in dreaming during rapid-eye-movement sleep ( Martial et al, 2020a ) do not only acknowledge a psychological basis of NDEs ( Lange et al, 2004 ) but also, and primarily, a neurophysiological basis becoming noticeable in ASCs. This NDE definition opens the door to the understanding of NDEs via the knowledge of the neurophysiological bases of the generation of wakefulness and awareness and of changes in these basic attributes of consciousness (e.g., Sperry, 1968 ; Crick and Koch, 1990 ; Edelman, 1992 ; Baars, 1993 ; Aru et al, 2012 ; Damasio, 2012 ; Dehaene, 2014 ; Tononi et al, 2016 ; Gazzaniga, 2018 ; Ehret and Romand, 2022 ). The definition of an authentic NDE or RED by listing necessary presence and absence of components in the NDE reports has been criticized ( Evrard et al, 2022 ) as “ a very risky strategy, which truncates the NDE phenomenon to avoid confronting what the last decades of research have revealed.”…”
Section: How Have Near-death Experiences Been Defined?mentioning
confidence: 99%
See 3 more Smart Citations
“…The NDE definition by Charland-Verville et al (2020) and the consideration that some situations of NDEs may refer to disconnected consciousness as, for example, observed in dreaming during rapid-eye-movement sleep ( Martial et al, 2020a ) do not only acknowledge a psychological basis of NDEs ( Lange et al, 2004 ) but also, and primarily, a neurophysiological basis becoming noticeable in ASCs. This NDE definition opens the door to the understanding of NDEs via the knowledge of the neurophysiological bases of the generation of wakefulness and awareness and of changes in these basic attributes of consciousness (e.g., Sperry, 1968 ; Crick and Koch, 1990 ; Edelman, 1992 ; Baars, 1993 ; Aru et al, 2012 ; Damasio, 2012 ; Dehaene, 2014 ; Tononi et al, 2016 ; Gazzaniga, 2018 ; Ehret and Romand, 2022 ). The definition of an authentic NDE or RED by listing necessary presence and absence of components in the NDE reports has been criticized ( Evrard et al, 2022 ) as “ a very risky strategy, which truncates the NDE phenomenon to avoid confronting what the last decades of research have revealed.”…”
Section: How Have Near-death Experiences Been Defined?mentioning
confidence: 99%
“…Here, we will open the perspective to scientifically address and validate NDEs in the context of brain functions. Their relationship to consciousness has been a major subject of studies in the neurosciences for a long time (e.g., Ehret and Romand, 2022 ). Such a neuro-functional approach may offer valuable ideas for psychiatric and psychologic learning- and/or medication-based treatment of persons who suffer from their experiences.…”
Section: How Have Near-death Experiences Been Defined?mentioning
confidence: 99%
See 2 more Smart Citations
“…On l'a lu et sans doute aussi constaté : durant les deux dernières années, les jeunes ont subi de plein fouet les mesures politico sanitaires. A l'âge de la transformation radicale, de la projection existentielle, de la césure avec l'univers connu de l'enfance et de l'ouverture quelques exceptions de moments de conscience près (Ebner & Hameroff, 2011;Ehret & Romand, 2022;Eriksson, 2017;Frigato, 2021;Hutchinson, 2019;Koch et al, 2016;Polak & Marvan, 2018;Tononi & Koch, 2008;Yaron et al, 2022). (Kohler et al, 2002).…”
Section: Résuméunclassified